Guy D. R. Sanders, Jennifer Palinkas, Ioulia Tzonou-Herbst, with James Herbst. Ancient Corinth: Site Guide, 7th Edition. pp. 208, with col. plates. 2018. Princeton NJ: The American School of Classical Studies at Athens. ISBN 978-0-87661-661-1, hardcover - Valente, Rossana (Journal of Greek Archaeology, 2020)
Since the beginning of the excavations in Ancient Corinth by the American School of Classical Studies at Athens in 1896, a multi-period, intricate stratigraphy of the urban landscape of this site has been unravelled. This century-long history of excavations in Ancient Corinth has been previously disseminated by six editions of the site guide published by the American School of Classical Studies at Athens. Previous editions were curated by the ASCSA director Rhys Carpenter in 1928 and in 1933; the scholar Charles Morgan in 1936; Oscar Broneer in 1947 and 1951, whose 1951 edition was revisited by Robert Scranton in 1954; and, finally, Corinth director Henry Robinson in 1960.